If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 3 = 15 + 3x Reorder the terms: 3 + 9x = 15 + 3x Solving 3 + 9x = 15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 9x + -3x = 15 + 3x + -3x Combine like terms: 9x + -3x = 6x 3 + 6x = 15 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 6x = 15 + 0 3 + 6x = 15 Add '-3' to each side of the equation. 3 + -3 + 6x = 15 + -3 Combine like terms: 3 + -3 = 0 0 + 6x = 15 + -3 6x = 15 + -3 Combine like terms: 15 + -3 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 6x^2-17xy-3y^2+22x+10y-8=0 | | 5x-3=12x+3 | | 8x+9=-7 | | 250+0.25x=x | | 5x^4=6x^2+2 | | 2x^2-xy+5x-2y+2=0 | | 6x-40=x-36 | | 3x-20=x-18 | | 4x+x+7=44 | | 8x+48=2x+90 | | 6x-30=50-4x | | 6x-1=104-9x | | 11x+6=2x+87 | | -5=2x+13 | | 12=7x+-4 | | 4m+2=-3m+16 | | 4x-5=103-8x | | 5(x-3)+12= | | 6x-30=42-6x | | 5m-21-3m+38=-5 | | 4+8(x-2)=4 | | m-5-4m=-18 | | 2x+3.2=0 | | y(y+14)=48 | | -6(t-8)-(t+6)=7 | | 7p+4=2p+19 | | 4x*2-4=0 | | 2(x+2)=3(x-4) | | 7x-25=10 | | 1=15y-x | | 121-7x=9x+23 | | 140-5x=4x+23 |